Trend and Variability Analysis for Forecasting of Temperature in Bangladesh (Journal of Environmental Science and Natural Resources, 2012)
An attempt was made to investigate the trend and variability pattern for decadal, annual and seasonal (three crop seasons) average dry bulb temperature (ADBT) for the six divisional stations of Bangladesh namely Dhaka, Khulna, Rajshahi, Barisal, Sylhet and Chittagong. The monthly ADBT for 2009-2012 is forecasted using the univariate Box-Jenkins ARIMA (autoregressive integrated moving average) modelling technique. The rates of linear trend for annual average dry bulb temperature (ADBT) were found negative for Rajshahi and Barisal but positive for Dhaka, Khulna, Sylhet and Chittagong. The rates for Seasonal ADBT were positive for all the three seasons for Dhaka and Chittagong, but negative for all the three seasons for Barisal while positive for Kharif and Rabi seasons and negative for Prekharif seasons for Khulna and Sylhet. The rates were positive for Kharif season but negative for Prekharif and Rabi seasons for Rajshahi. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11589 J. Environ. Sci. & Natural Resources, 5(1): 243-252, 2012